KARAKTERISTIK DAN STRATEGI KOPING DENGAN STRES PASIEN KANKER PAYUDARA DALAM MENJALANI KEMOTERAPI - Putri, Sri Burhani; Hamid, Achir Yani Syuhaemi; Priscilla, Vetty (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2017)
Breast cancer is main cause of death in women .One therapy carried out to the treatment of disease breast cancer is chemotherapy .Chemotherapy has adverse side effects physical and psychological so that the patient breast cancer that had chemotherapy susceptible are subjected to stress .Stress influenced by several factors including the characteristics and strategy koping used by patients .The purpose of this research is have a description of relations the characteristics and strategy koping to stress patients breast cancer that had chemotherapy .This research using design cross sectional study with the sample collection in accidental sampling .Data analyzed by the in bivariat and multivariate with the results of variable are associated with stress patients breast cancer that had chemotherapy between other characteristic age ( pvalue = 0.00 ) , a long time since diagnosis of cancer ( pvalue = 0.03 ) , long had chemotherapy ( pvalue = 0.00 ) and strategies koping seeks support social ( pvalue = 0.00 ) , seeks support spiritual ( pvalue = 0.00 ) variable dominant relating to stress that is strategy koping seeks support spiritual ( coeffecients B = -1.139 )